Index Fund Performance in China and Tracking Error Analysis - Zhu, Leting (2007)
The aim of this dissertation is to evaluate the performance of China's index funds market. The study presents the performance of the index funds during the period from 15th.September 2005 to 20th August 2007. The academic basis for the index funds and tracking error analysis are reviewed. Different forms of tracking error calculations and information ratio are chosen to examine the performance of sample data which includes 8 pure index funds in China. The calculation results indicate that China's index funds have perfectly tracked the benchmark indexes and control the tracking error to 0.8%. However, index fund managers still have a long way to go due to the given defects in China's emerging capital market such as high impact costs. This study is an attempt to fulfill the blank in the academic field of China's index funds market.